INTEGRASI TEKNOLOGI DAN PRINSIP PSIKOLOGI PENDIDIKAN DALAM MENDESAIN PEMBELAJARAN ERA DIGITAL: STUDI LITERATUR - Amahoru, Archristhea; Stavinibelia, Stavinibelia; Fauzi, Muhammad Sukron; Fitriana, Septi; Arsyad, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has brought significant changes in the field of education, requiring innovation in designing effective learning. This study aims to analyze the integration of technology and educational psychology principles in learning design in the digital era through a systematic literature review approach. Data were collected from various scientific databases, such as Google Scholar, ScienceDirect, Springer, and Taylor & Francis, covering publications from 2020 to 2025. The results show that the integration of technology supported by educational psychology principles, such as cognitive theory, constructivism, and motivation, can enhance student engagement, learning effectiveness, and critical thinking skills. However, several challenges remain, including teachers’ limited competence in pedagogically integrating technology, inadequate infrastructure, and the lack of optimal integration among technology, pedagogy, and content aspects. Therefore, comprehensive strategies are needed, including strengthening teacher competencies, developing innovative instructional designs, and providing adequate policy support and facilities to optimize learning in the digital era